Young learner, diverse children: celebrating diversity in early childhood - Gonzalez, Virginia (Corwin, 2012)
Written as a guide for early childhood teachers, this book provides a model for meeting the educational needs of diverse, low socioeconomic status (SES), young children in Pre-K through Grade 3.This book offers a unique educational perspective that interfaces cognition, language, and culture; provides lesson plans and classroom-based alternative assessment tools that meet pedagogical and accountability purposes; and integrates standards across developmental levels and content areas. Using her experience in establishing a successful school laboratory for diverse preschoolers, the author presents real-life stories of early childhood teachers and their diverse young learners and parents as case studies and examples of best teaching practices.Young Learners, Diverse Children endorses an integrational and pluralistic approach to the linguistic and cultural adaptation of young diverse students and their families, in which they can maintain their diversity while assimilating into the American culture. This engaging, inspirational, and practical handbook helps teachers solve real-life challenges as they teach and facilitate learning for diverse young children and build partnerships with their families.